2014
DOI: 10.1063/1.4867066
|View full text |Cite
|
Sign up to set email alerts
|

Hard magnetohydrodynamic limit in 1/3 sawtooth like activity in LHD

Abstract: The optimization of LHD discharges in inward-shifted configurations with 1/3 sawtooth like activity is an open issue. These relaxation events limit the LHD performance driving a periodic plasma deconfinement. The aim of this study is to analyze the 1/3 sawtooth like activity in plasmas with different stability properties to foreseen the best operation conditions and minimize its undesired effects. We summarize the results of several MHD simulations for plasmas with Lundquist numbers between 10 5 and 10 6 in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(29 reference statements)
3
5
0
Order By: Relevance
“…The present model was already used to study the stability of PM during sawtooth-like events and internal collapses [88,89,90,91], TAE [68] and EIC [92] activity in LHD, indicating reasonable agreement with the observations. T th,0 n th,0 < β tot > V A0 (keV) (10 20 m −3 ) (%) (10 6 m/s) 4 0.3 1.8 3.98 Table 1.…”
Section: Equations and Numerical Schemesupporting
confidence: 80%
See 1 more Smart Citation
“…The present model was already used to study the stability of PM during sawtooth-like events and internal collapses [88,89,90,91], TAE [68] and EIC [92] activity in LHD, indicating reasonable agreement with the observations. T th,0 n th,0 < β tot > V A0 (keV) (10 20 m −3 ) (%) (10 6 m/s) 4 0.3 1.8 3.98 Table 1.…”
Section: Equations and Numerical Schemesupporting
confidence: 80%
“…The present model was already used to study the stability of PM during sawtooth-like events and internal collapses [85][86][87][88], TAE [65] and EIC [89] activity in LHD, indicating reasonable agreement with the observations.…”
Section: Equations and Numerical Schemesupporting
confidence: 80%
“…The present model was already used to study the linear stability of LHD plasma, particularly the AE destabilization by EP [22], AE stability of plasma with multiple EP populations [23], the effect of the tangential NBI current drive on the stability of pressure and EP driven MHD modes [24] as well as EIC stabilization strategies [25], showing a reasonable agreement with the observations. In addition, nonlinear studies were performed reproducing the sawtooth-like and internal collapse events observed in LHD plasma [26][27][28][29].…”
Section: T I (Kev)mentioning
confidence: 99%
“…In the case of the hard MHD limit, the instability spreads on modes with different helicities along the plasma and the events driven are global relaxations. The events studied in the soft MHD limit are the non resonant 1/3 and 1/2 sawtooth like events, and the internal disruptions and resonant 1/3 sawtooth like events in the hard MHD limit 9,11,12 . There is experimental evidence of these events in LHD, expect in the case of the internal disruption 13 .…”
Section: Introductionmentioning
confidence: 99%